In vivo imaging with a cell-permeable porphyrin-based MRI contrast agent - Lee, Taekwan (2010)
Magnetic resonance imaging (MRI) with molecular probes offers the potential to monitor physiological parameters with comparatively high spatial and temporal resolution in living subjects. For detection of intracellular analytes, construction of cell-permeable imaging agents remains a challenge. Here we show that a porphyrin-based MRI molecular imaging agent, Mn-(DPA-C(2))(2)-TPPS(3), effectively penetrates cells and persistently stains living brain tissue in intracranially injected rats. Chromogenicity of the probe permitted direct visualization of its distribution by histology, in addition to MRI. Distribution was concentrated in cell bodies after hippocampal infusion. Mn-(DPA-C(2))(2)-TPPS(3) was designed to sense zinc ions, and contrast enhancement was more pronounced in the hippocampus, a zinc-rich brain region, than in the caudate nucleus, which contains relatively little labile Zn(2+). Membrane permeability, optical activity, and high relaxivity of porphyrin-based contrast agents offer exceptional functionality for in vivo imaging.